The main cannabinoids content in hashish samples seized in Israel and Czech Republic. Issue 3 (2nd July 2016) - Hanuš, Lumír O.; Levy, Rina; De La Vega, Dafna; Katz, Limor; Roman, Michael; Tomíček, Pavel
Abstract : Cannabis, both herbal and resin, has been the most popular illicit drug in Israel in recent years. Until 2005, the main sources of cannabis resin (known also as hashish) to the Israeli drug market were Lebanon and India. Hashish from these sources can be distinguished by its external appearance. The aim of this study was to determine if there is any difference in the quality of the hashish from each source. For this purpose, we quantified the main cannabinoids, cannabidiol (CBD), Δ 9 -tetrahydrocannabinol (Δ 9 -THC), and cannabinol (CBN) of hashish from different police seizures of known origins, Lebanon, India and Morocco, that had been submitted to the Analytical Chemistry Laboratory of the Division of Identification and Forensic Science at the Israeli National Police Headquarters and subsequently to the Hebrew University for quantitative analysis. The results, based on many different seizures, showed that the average CBD content of hashish from Lebanon varied from 5.69% to 12.79% (an average 8.98 ± 0.59%), THC of hashish from Lebanon varied from 0.93% to 4.20% (an average of 2.38 ± 0.27 %), CBD of hashish from Morocco varied from 1.52% to 5.14% (an average of 3.72 ± 0.19%), THC of hashish from Morocco varied from 5.08% to 13.41% (an average of 9.21 ± 0.40%), CBD of hashish from India varied from 0.78% to 13.13% (an average of 4.59 ± 1.07%), and THC of hashish from India varied from 0.53% to 16.45% (an average of 6.35 ± 1.50%), At the same time, several other cannabinoids present in the samples in lower amounts were identified (cannabidivarol, CBDV; cannabicitran; Δ 9 -tetrahydrocannabivarol, Δ 9 -THCV; cannabivarol, CBV; cannabicyclol, CBL; cannabichromene, CBC; cannabielsoin, CBE; Δ 8 -THC; and cannabigerol, CBG). The samples, predominantly from Lebanon, Morocco, and India, were evaluated for chemical phenotype (drug type and fiber type) to determine the geographical origin of these samples. Indian hashish, seized by Czech Republic authorities, was analyzed qualitatively for many cannabinoids and terpenes. In this sample three new cannabinoids were identified: cannabiorcochromene, cis -Δ 9 -tetrahydrocannabivarol, and cannabinerol.